Efficient chloride ion migration-resistant auxiliary cementing material as well as preparation method and application of efficient chloride ion migration-resistant auxiliary cementing material

Through the synergistic effects of fly ash, slag, metakaolin, activated desulfurization gypsum and waste glass powder, high-efficiency chloride ion migration auxiliary gelling materials are prepared, and the complex and costly preparation of chloride ion migration materials in the existing technology is solved. , realizes high-efficiency chloride ion migration resistance and environmentally friendly cement concrete applications, protects steel bars and reduces the amount of cement.

CN119263660APending Publication Date: 2025-01-07GUANGZHOU INSTITUTE OF BUILDING SCIENCE CO LTD

Patent Information

Application Number
CN202411275870.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The preparation process of existing chloride ion migration-resistance auxiliary gelling materials is complex and has high cost, which may affect cement hydration, and is insufficient in efficiency, so it cannot fully protect the steel bars from rust.

Method used

Using fly ash, slag, metakaolin, activated desulfurization gypsum and waste glass powder, high-efficiency chloride ion migration-resistance auxiliary cementitious materials are prepared through a simple mixing and stirring process, and the synergistic effect of these materials is used to improve the cement concrete Chloride ion transport resistance and reduce cement usage.

Benefits of technology

It significantly improves the migration resistance of cement concrete to chloride ions, protects steel bars from rust, reduces the amount of cement, realizes low-carbon and environmentally friendly industrial application, and improves the durability and recycling value of building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263660A_ABST
    Figure CN119263660A_ABST
Patent Text Reader

Abstract

The invention provides an efficient chloride ion migration prevention auxiliary cementing material and a preparation method and application thereof, the efficient chloride ion migration prevention auxiliary cementing material comprises the following components by weight: 10-100 parts of fly ash, 10-100 parts of slag, 10-20 parts of metakaolin, 2-8 parts of activated desulfurized gypsum, 1-5 parts of a C-S-H nano crystal nucleus early strength agent, and 5-10 parts of waste glass powder. The fly ash, the slag, the desulfurized gypsum, the waste glass powder and other solid wastes are utilized on a large scale and compounded with the metakaolin and the C-S-H nano crystal nucleus early strength agent to prepare the efficient chloride ion migration resistance auxiliary cementing material, so that the compactness of a cement-based material system is increased, the pore distribution of the cement-based material is refined, the chloride ion migration resistance is enhanced, and the cement-based material has the advantages that the cement-based material can be recycled; the cement concrete can effectively improve the ability of cement concrete to resist the corrosion of chloride ions in the external environment, increases the value of cyclic utilization of construction wastes, and has the advantages of simple preparation process, no need of steam curing, low carbon and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a high-efficiency chloride ion migration blocking auxiliary gelling material and a preparation method and application thereof. Background Art

[0002] In the field of construction, steel corrosion caused by chloride salts is one of the main reasons for the long-term durability degradation of concrete structures. The chloride ions in chloride salts are divided into free chloride ions and bound chloride ions. Bound chloride ions are chloride ions that are physically adsorbed and chemically bound on the surface of the pore structure, and will not cause harm to the concrete structure. Due to their small ion radius and strong penetration ability, free chloride ions can pass through the concrete protective layer and accumulate near the surface of the steel bars, and produce ion depolarization and conductivity with the steel bars to destroy the passivation film on the surface of the steel bars, and then the steel bars are depassivated, resulting in cracking and peeling of the concrete protective layer, which in turn affects the long-term service life of the concrete structure. The migration barrier of cement-based materials refers to the fact that the migration process of free chloride ions in concrete is mainly driven by concentration gradient and relies on the liquid phase as the migration medium. The distribution of the liquid phase in cement depends on the pore distribution structure of the cement-based materials. Therefore, refining the pore distribution of cement-based materials, increasing the density of the material system, cutting off the chloride ion migration channel, and preventing free chloride ions from reaching the steel bar surface through the pore solution can prevent chloride ions from corroding the steel bars and improve the chloride ion migration barrier of cement-based materials.

[0003] At present, studies have shown that adding chemical admixtures, mineral admixtures and nanomaterials to cement-based materials can refine the pore structure of cement-based materials, improve the free chloride ion migration resistance, reduce the free chloride ion content, prevent chloride ion migration, and thus improve the service life of reinforced concrete structures. However, chemical admixtures prevent chloride ions from contacting the steel bars by forming a protective film on the surface of the steel bars, but they cannot provide adequate protection. The steel bars are still at risk of corrosion in the weak areas of the passivation film; directly adding mineral admixtures to concrete has a certain effect on the early strength of concrete. At the same time, existing research often focuses on the influence of a single factor on the chloride ion migration resistance of cement-based materials, and there is currently little research on the synergistic influence of multiple factors on the chloride ion migration resistance of cement-based materials.

[0004] Chinese patent CN109485296B "A swelling and migration-blocking microcapsule chloride ion curing agent and its preparation method and application" uses nano-silicon dioxide and stearic acid as capsule wall materials to coat the chloride ion migration-blocking substances sodium alginate and overburned lime powder, which can improve the concrete's resistance to the migration of free chloride ions. However, the preparation process of the above microcapsules is complicated and costly, which may affect cement hydration. At the same time, microcrack triggering leads to insufficient mechanical triggering efficiency of microcapsules. Therefore, there is an urgent need to develop cheap, efficient, and environmentally friendly chloride ion efficient migration-blocking materials.

[0005] The rapid growth of the industrial economy is accompanied by the generation of a large amount of solid waste. Considering the use of bulk solid waste to prepare cementitious materials is conducive to the resource utilization and secondary utilization of industrial solid waste, reducing the pollution of the environment by industrial solid waste, and is crucial to solving the problem of sustainable development.

[0006] Therefore, using industrial solid waste to prepare a high-efficiency chloride ion migration-blocking auxiliary cementitious material is of great significance for improving the chloride ion migration resistance of cement-based materials, reducing the amount of cement used, and achieving energy conservation, emission reduction, low-carbon and environmentally friendly modern industrialization requirements. Summary of the invention

[0007] In view of the problems that the existing chloride ion migration blocking auxiliary cementitious materials have complex preparation processes, high costs, possible influence on cement hydration and insufficient efficiency, the present invention provides a high-efficiency chloride ion migration blocking auxiliary cementitious material and a preparation method and application thereof, and solid wastes such as fly ash, slag, desulfurized gypsum, and waste glass powder are utilized on a large scale, and compounded with metakaolin and CSH nanocrystalline core early strength agent to prepare the high-efficiency chloride ion migration blocking auxiliary cementitious material, which can effectively improve the ability of cement concrete to resist chloride ion corrosion in the external environment, has a simple preparation process, does not require steaming, and is low-carbon and environmentally friendly.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] A high-efficiency chloride ion migration blocking auxiliary gelling material comprises the following components by weight: 10-100 parts of fly ash, 10-100 parts of slag, 10-20 parts of metakaolin, 2-8 parts of activated desulfurized gypsum, 1-5 parts of CSH nanocrystalline core early strength agent, and 5-10 parts of waste glass powder.

[0010] Furthermore, the activated desulfurized gypsum is prepared by the following method:

[0011] The desulfurized gypsum is kept at 750°C for 3 hours, and then ball-milled for 30 minutes after cooling to obtain the activated desulfurized gypsum; the CaSO4 content of the activated desulfurized gypsum is greater than 92%, and the specific surface area is ≥400m 2 / kg.

[0012] Furthermore, the fly ash is Class F fly ash, and the residue on a 45 μm square hole sieve is less than 20%.

[0013] Furthermore, the slag is S95 grade slag with a specific surface area of ​​≥450m 2 / kg.

[0014] Furthermore, the specific surface area of ​​the metakaolin is ≥500m 2 / kg.

[0015] Furthermore, the CSH nanocrystalline core early strength agent is a solid powder with a calcium-silicon ratio of 1.0-1.5 and an average particle size of 100-200 nm.

[0016] Furthermore, the waste glass powder has a SiO2 content of 55%-70%, a CaO content of 10%-20%, and a Na2O content of 10-20%, wherein the particle size of the waste glass powder is not greater than 120 μm.

[0017] Another object of the present invention is to provide a method for preparing a highly efficient chloride ion migration-blocking auxiliary gelling material.

[0018] A method for preparing a high-efficiency chloride ion migration-blocking auxiliary gelling material according to any of the above items, characterized in that it comprises the following steps:

[0019] S1. Weigh fly ash, slag, kaolin, activated desulfurized gypsum, CSH nanocrystalline core early strength agent and waste glass powder according to the required ratio to obtain a mixed dry material;

[0020] S2. Stir the mixed dry materials at a rate of 60-80 rpm for 2-3 minutes to obtain the chloride ion efficient migration blocking auxiliary gelling material.

[0021] Another object of the present invention is to provide an application of a highly efficient chloride ion migration blocking auxiliary gelling material.

[0022] An application of the above-mentioned high-efficiency chloride ion migration blocking auxiliary cementitious material in cement concrete.

[0023] Furthermore, the method for applying the high-efficiency chloride ion migration blocking auxiliary cementitious material in cement concrete comprises the following steps:

[0024] Step 1: Weigh cement and high-efficiency chloride ion migration blocking auxiliary cementitious material according to the required ratio, and stir at a speed of 60-80 rpm for 2-3 minutes to obtain a mixture;

[0025] Step 2, adding water to the mixture obtained in step 1, stirring at a rate of 60-80 rpm for 2-3 minutes and then at a rate of 120-150 rpm for 5-6 minutes, pouring the slurry to fill the mold and vibrating it, removing the mold after curing for 1 day, sealing and curing, and obtaining cement concrete containing high-efficiency chloride ion migration blocking auxiliary cementitious material;

[0026] The proportion of the cement, the high-efficiency chloride ion migration blocking auxiliary cementitious material and water, calculated by weight fraction, is: 100 parts of cement, 38-243 parts of the high-efficiency chloride ion migration blocking auxiliary cementitious material and 70 parts of water.

[0027] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0028] The invention provides a high-efficiency chloride ion migration blocking auxiliary cementitious material, which is prepared by compounding fly ash, slag, metakaolin, activated desulfurized gypsum, CSH nanocrystalline core early strength agent and waste glass powder, and gives full play to the synergistic effect of multiple solid wastes such as fly ash, slag, desulfurized gypsum, waste glass powder and other industrial solid wastes; the alkalinity of the cement-based material system is improved by the active sodium contained in the waste glass powder, and the volcanic ash activity of the fly ash, slag and metakaolin is further stimulated to generate C-(N)-ASH gel with a high cross-linking degree, and the chloride ion curing ability of cement concrete is improved, thereby realizing high-efficiency chloride ion migration blocking; at the same time, the active aluminum dissolved from the slag and metakaolin and the calcium sulfate in the activated desulfurized gypsum are used to generate calcium sulfonate, so that the microstructure of the cement-based material is compacted on a smaller scale, the pore distribution of the cement-based material is refined, the chloride ion migration blocking property is enhanced, the steel bars are protected from rust, and the cement dosage is significantly reduced, thereby increasing the recycling value of construction waste.

[0029] The present invention provides hydration nucleation sites for calcium-silicon-aluminum materials such as fly ash, slag and metakaolin through the CSH nanocrystalline core admixture in the high-efficiency chloride ion migration-assisted cementitious material system, thereby accelerating the active Ca 2+ , Si 4+ and Al 3+ The precipitation significantly increases the concentration of active ions in the system, promotes the precipitation and growth of hydration products in the system, increases the density of the cement-based material system, adsorbs some free chloride ions, enhances the density of the matrix and the chloride ion migration resistance of the material, and enables it to be used as a high-efficiency chloride ion migration-resistant auxiliary cementitious material for the preparation of cement concrete.

[0030] The preparation process of the invention is simple. After mixing the component materials, a high-efficiency chloride ion migration-blocking auxiliary cementitious material can be obtained. The material does not require steaming, is low-carbon and environmentally friendly, has a fast strength development rate, and exhibits significant environmental benefits and economic value, which is of positive significance for promoting the sustainable development of the construction industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0032] Figure 1 These are the microscopic SEM images of cement concrete used in the highly efficient chloride ion migration blocking auxiliary cementitious materials of Example 1 and Comparative Examples 1, 4, and 6 of the present application; (a) is Example 1 after 28 days of curing, (b) is Comparative Example 1 after 28 days of curing, (c) is Comparative Example 4 after 28 days of curing, and (d) is Comparative Example 6 after 28 days of curing. DETAILED DESCRIPTION

[0033] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.

[0034] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0035] The following examples are all cement pastes.

[0036] Example 1

[0037] A method for preparing a high-efficiency chloride ion migration-blocking auxiliary gelling material comprises the following steps:

[0038] The desulfurized gypsum is kept at 750° C. for 3 hours, and then ball-milled for 30 minutes after cooling to obtain the activated desulfurized gypsum.

[0039] S1. Weigh fly ash, slag, kaolin, activated desulfurized gypsum, CSH nanocrystalline core early strength agent and waste glass powder according to the required ratio to obtain a mixed dry material;

[0040] S2. Stir the mixed dry materials at a rate of 60 rpm for 2 minutes to obtain the chloride ion efficient migration blocking auxiliary gelling material.

[0041] The method for applying the chloride ion efficient migration blocking auxiliary cementitious material in cement concrete comprises the following steps:

[0042] Step 1: weigh cement and high-efficiency chloride ion migration blocking auxiliary cementitious material according to the required ratio, and stir at a speed of 60 rpm for 2 minutes to obtain a mixture;

[0043] Step 2: Add water to the mixture obtained in step 1, stir at a rate of 60 rpm for 2 minutes and then at a rate of 120 rpm for 5 minutes, pour the slurry to fill the mold and vibrate it, remove the mold after curing for 1 day, seal and cure, and obtain cement concrete containing high-efficiency chloride ion migration inhibition auxiliary cementitious material.

[0044] The cement concrete containing high-efficiency chloride ion migration-blocking auxiliary cementitious material comprises the following components, measured by weight: 100 parts of ordinary Portland cement, 35 parts of fly ash, 35 parts of slag, 20 parts of metakaolin, 8 parts of activated desulfurized gypsum, 10 parts of waste glass powder, 5 parts of CSH nanocrystalline core admixture, and 70 parts of water.

[0045] Example 2

[0046] A method for preparing a high-efficiency chloride ion migration-blocking auxiliary gelling material comprises the following steps:

[0047] The desulfurized gypsum is kept at 750° C. for 3 hours, and then ball-milled for 30 minutes after cooling to obtain the activated desulfurized gypsum.

[0048] S1. Weigh fly ash, slag, kaolin, activated desulfurized gypsum, CSH nanocrystalline core early strength agent and waste glass powder according to the required ratio to obtain a mixed dry material;

[0049] S2. Stir the mixed dry materials at a rate of 80 rpm for 2 minutes to obtain the chloride ion efficient migration blocking auxiliary gelling material.

[0050] The method for applying the chloride ion efficient migration blocking auxiliary cementitious material in cement concrete comprises the following steps:

[0051] Step 1: Weigh cement and high-efficiency chloride ion migration blocking auxiliary cementitious material according to the required ratio, and stir at a speed of 80 rpm for 3 minutes to obtain a mixture;

[0052] Step 2: Add water to the mixture obtained in step 1, stir at a rate of 80 rpm for 3 minutes and then at a rate of 150 rpm for 6 minutes, pour the slurry to fill the mold and compact it, remove the mold after curing for 1 day, seal and cure, and obtain cement concrete containing high-efficiency chloride ion migration blocking auxiliary cementitious material.

[0053] The cement concrete containing high-efficiency chloride ion migration-blocking auxiliary cementitious material comprises the following components, measured by weight: 100 parts of ordinary Portland cement, 20 parts of fly ash, 50 parts of slag, 10 parts of metakaolin, 2 parts of activated desulfurized gypsum, 5 parts of waste glass powder, 1 part of CSH nanocrystalline core admixture, and 70 parts of water.

[0054] Example 3

[0055] A method for preparing a high-efficiency chloride ion migration-blocking auxiliary gelling material comprises the following steps:

[0056] The desulfurized gypsum is kept at 750° C. for 3 hours, and then ball-milled for 30 minutes after cooling to obtain the activated desulfurized gypsum.

[0057] S1. Weigh fly ash, slag, kaolin, activated desulfurized gypsum, CSH nanocrystalline core early strength agent and waste glass powder according to the required ratio to obtain a mixed dry material;

[0058] S2. Stir the mixed dry materials at a rate of 70 rpm for 2 minutes to obtain the chloride ion efficient migration blocking auxiliary gelling material.

[0059] The method for applying the chloride ion efficient migration blocking auxiliary cementitious material in cement concrete comprises the following steps:

[0060] Step 1: Weigh cement and high-efficiency chloride ion migration blocking auxiliary cementitious material according to the required ratio, and stir at a speed of 70 rpm for 3 minutes to obtain a mixture;

[0061] Step 2: Add water to the mixture obtained in step 1, stir at a rate of 70 rpm for 3 minutes and then at a rate of 130 rpm for 6 minutes, pour the slurry to fill the mold and vibrate it, remove the mold after curing for 1 day, seal and cure, and obtain cement concrete containing high-efficiency chloride ion migration inhibition auxiliary cementitious material.

[0062] The cement concrete containing high-efficiency chloride ion migration-blocking auxiliary cementitious material comprises the following components, measured by weight: 100 parts of ordinary Portland cement, 10 parts of fly ash, 100 parts of slag, 15 parts of metakaolin, 5 parts of activated desulfurized gypsum, 10 parts of waste glass powder, 3 parts of CSH nanocrystalline core admixture, and 70 parts of water.

[0063] Example 4

[0064] A method for preparing a high-efficiency chloride ion migration-blocking auxiliary gelling material comprises the following steps:

[0065] The desulfurized gypsum is kept at 750° C. for 3 hours, and then ball-milled for 30 minutes after cooling to obtain the activated desulfurized gypsum.

[0066] S1. Weigh fly ash, slag, kaolin, activated desulfurized gypsum, CSH nanocrystalline core early strength agent and waste glass powder according to the required ratio to obtain a mixed dry material;

[0067] S2. Stir the mixed dry materials at a rate of 75 rpm for 2 minutes to obtain the chloride ion efficient migration blocking auxiliary gelling material.

[0068] The method for applying the chloride ion efficient migration blocking auxiliary cementitious material in cement concrete comprises the following steps:

[0069] Step 1: Weigh cement and high-efficiency chloride ion migration blocking auxiliary cementitious material according to the required ratio, and stir at a speed of 75 rpm for 3 minutes to obtain a mixture;

[0070] Step 2: Add water to the mixture obtained in step 1, stir at a rate of 70 rpm for 2 minutes and then at a rate of 140 rpm for 6 minutes, pour the slurry to fill the mold and compact it, remove the mold after curing for 1 day, seal and cure, and obtain cement concrete containing high-efficiency chloride ion migration inhibition auxiliary cementitious material.

[0071] The cement concrete containing high-efficiency chloride ion migration-blocking auxiliary cementitious material comprises the following components, measured by weight: 100 parts of ordinary Portland cement, 100 parts of fly ash, 10 parts of slag, 10 parts of metakaolin, 2 parts of activated desulfurized gypsum, 5 parts of waste glass powder, 1 part of CSH nanocrystalline core admixture, and 70 parts of water.

[0072] Comparative Example 1

[0073] A method for preparing cement concrete comprises the following steps:

[0074] Step 1: Weigh cement according to the required ratio and stir at a speed of 60 rpm for 2 minutes to obtain a mixture;

[0075] Step 2: add water to the mixture obtained in step 1, stir at a rate of 60 rpm for 2 minutes and then at a rate of 120 rpm for 5 minutes, pour the slurry to fill the mold and vibrate it, remove the mold after curing for 1 day, seal and cure, and obtain cement concrete without high-efficiency chloride ion migration blocking auxiliary cementitious material.

[0076] The cement concrete comprises the following components, by weight: 200 parts of ordinary Portland cement and 70 parts of water.

[0077] Compared with Example 1, the cement concrete of this comparative example does not add a high-efficiency chloride ion migration-blocking auxiliary cementitious material.

[0078] Comparative Example 2

[0079] A method for preparing a high-efficiency chloride ion migration-blocking auxiliary gelling material comprises the following steps:

[0080] The desulfurized gypsum is kept at 750° C. for 3 hours, and then ball-milled for 30 minutes after cooling to obtain the activated desulfurized gypsum.

[0081] S1. Weigh fly ash, slag, kaolin, activated desulfurized gypsum and waste glass powder according to the required ratio to obtain a mixed dry material;

[0082] S2. Stir the mixed dry materials at a rate of 60 rpm for 2 minutes to obtain the chloride ion efficient migration blocking auxiliary gelling material.

[0083] Compared with Example 1, this comparative example does not add CSH nanocrystalline core early strengthening agent.

[0084] The method for applying the chloride ion efficient migration blocking auxiliary cementitious material in cement concrete comprises the following steps:

[0085] Step 1: Weigh cement and high-efficiency chloride ion migration blocking auxiliary cementitious material according to the required ratio, and stir at a speed of 60 rpm for 2 minutes to obtain a mixture;

[0086] Step 2: Add water to the mixture obtained in step 1, stir at a rate of 60 rpm for 2 minutes and then at a rate of 120 rpm for 5 minutes, pour the slurry to fill the mold and vibrate it, remove the mold after curing for 1 day, seal and cure, and obtain cement concrete containing high-efficiency chloride ion migration inhibition auxiliary cementitious material.

[0087] The cement concrete containing high-efficiency chloride ion migration-blocking auxiliary cementitious material comprises the following components, measured by weight: 100 parts of ordinary Portland cement, 35 parts of fly ash, 35 parts of slag, 20 parts of metakaolin, 8 parts of activated desulfurized gypsum, 10 parts of waste glass powder, and 70 parts of water.

[0088] Comparative Example 3

[0089] A method for preparing a high-efficiency chloride ion migration-blocking auxiliary gelling material comprises the following steps:

[0090] The desulfurized gypsum is kept at 750° C. for 3 hours, and then ball-milled for 30 minutes after cooling to obtain the activated desulfurized gypsum.

[0091] S1. Weigh fly ash, slag, metakaolin, activated desulfurized gypsum, and CSH nanocrystalline core early strength agent according to the required ratio to obtain a mixed dry material;

[0092] S2. Stir the mixed dry materials at a rate of 60 rpm for 2 minutes to obtain the chloride ion efficient migration blocking auxiliary gelling material.

[0093] Compared with Example 1, this comparative example does not add waste glass powder.

[0094] The method for applying the chloride ion efficient migration blocking auxiliary cementitious material in cement concrete comprises the following steps:

[0095] Step 1: Weigh cement and high-efficiency chloride ion migration blocking auxiliary cementitious material according to the required ratio, and stir at a speed of 60 rpm for 2 minutes to obtain a mixture;

[0096] Step 2: Add water to the mixture obtained in step 1, stir at a rate of 60 rpm for 2 minutes and then at a rate of 120 rpm for 5 minutes, pour the slurry to fill the mold and vibrate it, remove the mold after curing for 1 day, seal and cure, and obtain cement concrete containing high-efficiency chloride ion migration inhibition auxiliary cementitious material.

[0097] The cement concrete containing high-efficiency chloride ion migration blocking auxiliary cementitious material comprises the following components by weight: 100 parts of ordinary Portland cement, 35 parts of fly ash, 35 parts of slag, 20 parts of metakaolin, 8 parts of activated desulfurized gypsum, 5 parts of CSH nanocrystalline core admixture, and 70 parts of water.

[0098] Comparative Example 4

[0099] A method for preparing a high-efficiency chloride ion migration-blocking auxiliary gelling material comprises the following steps:

[0100] S1. Weigh fly ash, slag, kaolin, CSH nanocrystalline core early strength agent and waste glass powder according to the required ratio to obtain a mixed dry material;

[0101] S2. Stir the mixed dry materials at a rate of 60 rpm for 2 minutes to obtain the chloride ion efficient migration blocking auxiliary gelling material.

[0102] Compared with Example 1, this comparative example does not add activated desulfurized gypsum.

[0103] The method for applying the chloride ion efficient migration blocking auxiliary cementitious material in cement concrete comprises the following steps:

[0104] Step 1: Weigh cement and high-efficiency chloride ion migration blocking auxiliary cementitious material according to the required ratio, and stir at a speed of 60 rpm for 2 minutes to obtain a mixture;

[0105] Step 2: Add water to the mixture obtained in step 1, stir at a rate of 60 rpm for 2 minutes and then at a rate of 120 rpm for 5 minutes, pour the slurry to fill the mold and vibrate it, remove the mold after curing for 1 day, seal and cure, and obtain cement concrete containing high-efficiency chloride ion migration inhibition auxiliary cementitious material.

[0106] The cement concrete containing high-efficiency chloride ion migration blocking auxiliary cementitious material comprises the following components by weight: 100 parts of ordinary Portland cement, 35 parts of fly ash, 35 parts of slag, 20 parts of metakaolin, 10 parts of waste glass powder, 5 parts of CSH nanocrystalline core admixture, and 70 parts of water.

[0107] Comparative Example 5

[0108] A method for preparing a high-efficiency chloride ion migration-blocking auxiliary gelling material comprises the following steps:

[0109] S1. Weigh fly ash, slag, kaolin, desulfurized gypsum, CSH nanocrystalline core early strength agent and waste glass powder according to the required ratio to obtain a mixed dry material;

[0110] S2. Stir the mixed dry materials at a rate of 60 rpm for 2 minutes to obtain the chloride ion efficient migration blocking auxiliary gelling material.

[0111] Compared with Example 1, the desulfurized gypsum in this comparative example is not activated.

[0112] The method for applying the chloride ion efficient migration blocking auxiliary cementitious material in cement concrete comprises the following steps:

[0113] Step 1: Weigh cement and high-efficiency chloride ion migration blocking auxiliary cementitious material according to the required ratio, and stir at a speed of 60 rpm for 2 minutes to obtain a mixture;

[0114] Step 2: Add water to the mixture obtained in step 1, stir at a rate of 60 rpm for 2 minutes and then at a rate of 120 rpm for 5 minutes, pour the slurry to fill the mold and vibrate it, remove the mold after curing for 1 day, seal and cure, and obtain cement concrete containing high-efficiency chloride ion migration inhibition auxiliary cementitious material.

[0115] The cement concrete containing high-efficiency chloride ion migration-blocking auxiliary cementitious material comprises the following components, measured by weight: 100 parts of ordinary Portland cement, 35 parts of fly ash, 35 parts of slag, 20 parts of metakaolin, 8 parts of desulfurized gypsum, 10 parts of waste glass powder, 5 parts of CSH nanocrystalline core admixture, and 70 parts of water.

[0116] Comparative Example 6

[0117] A method for preparing a high-efficiency chloride ion migration-blocking auxiliary gelling material comprises the following steps:

[0118] The desulfurized gypsum is kept at 750° C. for 3 hours, and then ball-milled for 30 minutes after cooling to obtain the activated desulfurized gypsum.

[0119] S1. Weigh fly ash, kaolin, activated desulfurized gypsum, CSH nanocrystalline core early strength agent and waste glass powder according to the required ratio to obtain a mixed dry material;

[0120] S2. Stir the mixed dry materials at a rate of 60 rpm for 2 minutes to obtain the chloride ion efficient migration blocking auxiliary gelling material.

[0121] Compared with Example 1, no slag was added in this comparative example.

[0122] The method for applying the chloride ion efficient migration blocking auxiliary cementitious material in cement concrete comprises the following steps:

[0123] Step 1: Weigh cement and high-efficiency chloride ion migration blocking auxiliary cementitious material according to the required ratio, and stir at a speed of 60 rpm for 2 minutes to obtain a mixture;

[0124] Step 2: Add water to the mixture obtained in step 1, stir at a rate of 60 rpm for 2 minutes and then at a rate of 120 rpm for 5 minutes, pour the slurry to fill the mold and vibrate it, remove the mold after curing for 1 day, seal and cure, and obtain cement concrete containing high-efficiency chloride ion migration inhibition auxiliary cementitious material.

[0125] The cement concrete containing high-efficiency chloride ion migration-blocking auxiliary cementitious material comprises the following components by weight: 100 parts of ordinary Portland cement, 35 parts of fly ash, 20 parts of metakaolin, 8 parts of activated desulfurized gypsum, 10 parts of waste glass powder, 5 parts of CSH nanocrystalline core admixture, and 70 parts of water.

[0126] The performance test of the cement concrete samples obtained in the above embodiments and comparative examples is carried out, and the experimental test method is as follows:

[0127] In order to further illustrate the advantages of the preparation method of the present invention, relevant performance tests were carried out on the cement concrete to which the high-efficiency chloride ion migration blocking auxiliary cementitious material prepared by the present invention was applied, including mechanical properties, water absorption rate and electric flux tests.

[0128] 28d compressive strength: 100mm×100mm×100mm cubic test blocks were prepared for each group. Three test specimens were used as a group for the compressive strength test, and the results were averaged. 28d compressive strength refers to the compressive strength of cement concrete after 28 days of curing under standard conditions. The higher the 28d compressive strength, the better the mechanical properties of cement concrete.

[0129] Water absorption rate: The samples with a curing age of 28 days were tested for water absorption rate. After drying in a 60°C oven to constant weight, they were cooled to room temperature and completely immersed in deionized water at 20°C. The test samples were taken out every 4 hours and the excess water on the surface was wiped off to make the samples reach a saturated surface dry state. The mass of the sample after water absorption was weighed and the mass of the water-retaining sample was recorded after it was kept constant. The water absorption rate indicates the ability of cement concrete to absorb water within a certain period of time. The lower the water absorption rate, the higher the durability and water resistance of cement concrete, and it can also better protect the steel bars from erosion.

[0130] Electric flux: According to GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", the electric flux test was conducted on the samples after curing for 28 days. Three samples were taken as a group during the electric flux test, and the results were averaged. Electric flux mainly refers to the conductivity of cement concrete in an electric field. Under the action of DC voltage, ions in the solution can quickly penetrate and move toward the positive electrode. Measuring the amount of electricity passing through in a certain period of time can reflect the ability of cement concrete to resist chloride ion penetration. The lower the electric flux, the stronger the ability of cement concrete to resist chloride ion migration.

[0131] The result is as follows:

[0132] ①28d compressive strength

[0133] Table 1 28d compressive strength of Examples 1-4 and Comparative Examples 1-6

[0134] serial number 28d compressive strength (MPa) Example 1 57.2 Example 2 58.4 Example 3 60.1 Example 4 57.3 Comparative Example 1 46.8 Comparative Example 2 51.5 Comparative Example 3 48.5 Comparative Example 4 52.2 Comparative Example 5 50.2 Comparative Example 6 47.8

[0135] It can be seen from Table 1 that the cement concretes to which the high-efficiency chloride ion migration blocking auxiliary cementitious material prepared by the technical solution of the present invention is applied, and the 28d compressive strength of Examples 1-4 all reaches above 55 MPa, and all have excellent mechanical properties.

[0136] Comparative Example 1 is ordinary cement concrete, and its 28d compressive strength is 46.8MPa, which is 18.2% lower than that of Example 1. This is because the CSH nanocrystalline core admixture and multiple solid wastes work synergistically to increase the density of cement-based materials and reduce the porosity of cement-based materials. Comparative Example 2 does not add CSH nanocrystalline core early strength agent, and its 28d compressive strength is 51.5MPa, which is 10.0% lower than that of Example 1, indicating that the addition of an appropriate amount of CSH crystal core admixture is beneficial to the improvement of mechanical properties. Comparative Example 3 does not add waste glass powder, and its 28d compressive strength is 48.5MPa, which is 15.2% lower than that of Example 1, indicating that waste glass powder can further stimulate the volcanic ash activity of fly ash, slag and metakaolin, exert the synergistic effect of multiple solid wastes, and refine the pores. In Comparative Example 4, no activated desulfurized gypsum was added, and the 28d compressive strength was 52.2MPa, which was 8.7% lower than that in Example 1. In Comparative Example 5, the desulfurized gypsum was not activated, and the 28d compressive strength was 50.2MPa, which was 12.2% lower than that in Example 1. This is because the unactivated desulfurized gypsum contains more impurities, which is not conducive to the formation of hydration products and has a greater negative impact on cement-based materials. In Comparative Example 6, no slag was added, and the 28d compressive strength was 47.8MPa. The compressive strength was the worst among all comparative examples except Comparative Example 1 of ordinary concrete, which was 16.4% lower than that in Example 1. This is because the lack of slag reduced the content of active aluminum ions and active calcium ions in the system, which was not conducive to the precipitation and growth of hydration products, and reduced the density of the cement-based material system.

[0137] ②Water absorption

[0138] Table 2 Water absorption of Examples 1-4 and Comparative Examples 1-6

[0139]

[0140]

[0141] It can be seen from Table 2 that the water absorption rates of the cement concretes to which the high-efficiency chloride ion migration blocking auxiliary cementitious material prepared by the technical solution of the present invention is applied are all lower than 5.5% in Examples 1-4, among which the water absorption rate of Example 3 is the lowest, which is 4.7%, indicating that the density is high and the concretes exhibit excellent durability, water resistance and erosion resistance.

[0142] Comparative Example 1 is ordinary cement concrete, and its water absorption rate is 6.5%, which is 27.4% higher than that of Example 1; Comparative Example 2 without adding CSH nanocrystalline core early strength agent is 5.8%, and Comparative Example 3 without adding waste glass powder is 6.3%, indicating that the addition of CSH nanocrystalline core admixture and waste glass powder can improve the density of the material system, thereby preventing water molecules from penetrating from the sample surface into the material interior, wherein the CSH nanocrystalline core admixture has a greater influence on the density of the material system; the water absorption rates of Comparative Examples 4 and 5 are 5.9% and 6.2%, respectively, which are 15.7% and 21.6% higher than that of Example 1, respectively, because the activated desulfurized gypsum can generate calcium sulfonate with the active aluminum ions in the system, further improving the density of the system; the water absorption rate of Comparative Example 6 is 6.7%, which is 31.4% higher than that of Example 1, because the lack of aluminum phase affects the generation of hydration products.

[0143] ③Electric flux

[0144] Table 3 Electric flux test of Examples 1-4 and Comparative Examples 1-6

[0145]

[0146]

[0147] It can be seen from Table 3 that the cement concrete to which the high-efficiency chloride ion migration blocking auxiliary cementitious material prepared by the technical solution of the present invention is applied has an electric flux of less than 1300C in Examples 1-4, showing excellent chloride ion migration blocking ability.

[0148] The electric flux of the comparative example 1 is 1715C, which is 36.5% higher than that of the example 1. The electric flux of the comparative example 2 without adding the CSH nanocrystalline core early strength agent and the comparative example 3 without adding the waste glass powder are 1546C and 1621C respectively, which are higher than the electric flux of the example 1. This is because the active sodium contained in the waste glass powder increases the alkalinity of the cement-based material system, further stimulates the volcanic ash activity of the fly ash, slag and metakaolin, generates C-(N)-ASH gel with high cross-linking degree, improves the migration resistance of chloride ions, and at the same time, the CSH nanocrystalline core is added. The calcium ions and silicon ions dissolved by the agent promote the formation of hydration products; the electric fluxes of Comparative Examples 4 and 5 are 1476C and 1645C, respectively, which are 17.5% and 31.0% higher than the electric flux of Example 1, respectively. This is because the active aluminum in the system and the calcium sulfate in the activated desulfurized gypsum generate needle-shaped calcium sulfonate, which further refines the pores and improves the density of the cement-based material, thereby reducing the migration rate of free chloride ions and improving the chloride ion migration resistance of the system. The unactivated desulfurized gypsum contains impurities and less active ions are dissolved, which further affects the formation of hydration products. The electric flux of Comparative Example 6 is 1697C, which is 35.1% higher than that of Example A. This is because the lack of slag leads to the lack of aluminum phase, which affects the formation of hydration gel and further reduces the chloride ion migration resistance.

[0149] The samples of Example 1, Comparative Example 1, Comparative Example 4 and Comparative Example 6 were subjected to SEM test, and the results are as follows: Figure 1 As shown, Figure 1 These are the microscopic SEM images of cement concrete used in the highly efficient chloride ion migration blocking auxiliary cementitious materials of Example 1 and Comparative Examples 1, 4, and 6 of the present application; (a) is Example 1 after 28 days of curing, (b) is Comparative Example 1 after 28 days of curing, (c) is Comparative Example 4 after 28 days of curing, and (d) is Comparative Example 6 after 28 days of curing.

[0150] As can be seen from the figure, at the age of 28 days, compared with comparative example 1, the surface roughness of example 1 increased and the cracks were less, which means that more hydration products were produced on the surface, blocking the migration channel of chloride ions. At the same time, the hydration reaction of fly ash and slag particles was complete and it was difficult to identify them in the figure. In addition, some needle-shaped hydration products can be seen in example 1, which indicates the formation of ettringite. Figure 1 In (c), it can be found that there is no needle-shaped hydration product on the surface of Comparative Example 4. This is because the lack of activated desulfurized gypsum affects the formation of ettringite in the system. Figure 1 In (d), there are more pores on the surface of Comparative Example 6. This is because the lack of slag reduces the active aluminum phase in the system, further affecting the formation of hydration products.

[0151] In summary, the present invention prepares a high-efficiency chloride ion migration-blocking auxiliary cementitious material by compounding fly ash, slag, metakaolin, activated desulfurized gypsum, CSH nanocrystalline core early strength agent, and waste glass powder, giving full play to the synergistic effect of multiple solid wastes of industrial solid wastes such as fly ash, slag, and waste glass powder; the waste glass powder stimulates the volcanic ash activity of fly ash, slag, and metakaolin to generate C-(N)-ASH gel, improves the chloride ion curing ability of cement concrete, and thus achieves high-efficiency chloride ion migration; at the same time, ettringite is generated by slag and metakaolin, the microstructure of cement-based materials is compacted on a smaller scale, the pore distribution of cement-based materials is refined, the chloride ion migration resistance is enhanced, the steel bars are protected from rust, and the cement dosage is significantly reduced, the recycling value of construction waste is increased, and the CSH nanocrystalline core admixture in the system provides hydration nucleation sites for calcium-silicon-aluminum materials such as fly ash, slag, and metakaolin, accelerating the active Ca 2+ , Si 4+ and Al 3+ It can promote the precipitation and growth of hydration products of the system, increase the density of cement-based material system, absorb some free chloride ions, enhance the density of the matrix and the chloride ion migration resistance of the material, so that it can be used as a high-efficiency chloride ion migration auxiliary cementitious material for the preparation of cement concrete. At the same time, the preparation process is simple, no steam curing is required, low-carbon and environmentally friendly, and the strength development rate is fast, showing significant environmental benefits and economic value, which has positive significance for promoting the sustainable development of the construction industry.

[0152] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A highly efficient chloride ion migration-blocking auxiliary gelling material, characterized in that: The invention comprises the following components by weight: 10-100 parts of fly ash, 10-100 parts of slag, 10-20 parts of metakaolin, 2-8 parts of activated desulfurized gypsum, 1-5 parts of CSH nano-crystalline core early strength agent and 5-10 parts of waste glass powder.

2. A high-efficiency chloride ion migration-blocking auxiliary gelling material according to claim 1, characterized in that: The activated desulfurized gypsum is prepared by the following method: The desulfurized gypsum is kept at 750° C. for 3 hours, and then ball-milled for 30 minutes after cooling to obtain the activated desulfurized gypsum; The activated desulfurized gypsum has a CaSO4 content greater than 92% and a specific surface area of ​​400 m 2 / kg.

3. A high-efficiency chloride ion migration-blocking auxiliary gelling material according to claim 1, characterized in that: The fly ash is F-type fly ash, and the residue on a 45 μm square sieve is less than 20%.

4. A high-efficiency chloride ion migration-blocking auxiliary gelling material according to claim 1, characterized in that: The slag is S95 grade slag with a specific surface area of ​​≥450m 2 / kg.

5. A high-efficiency chloride ion migration-blocking auxiliary gelling material according to claim 1, characterized in that: The specific surface area of ​​the metakaolin is ≥500m 2 / kg.

6. A high-efficiency chloride ion migration-blocking auxiliary gelling material according to claim 1, characterized in that: The CSH nanocrystalline core early strength agent is solid powder, with a calcium-silicon ratio of 1.0-1.5 and an average particle size of 100-200nm.

7. A high-efficiency chloride ion migration-blocking auxiliary gelling material according to claim 1, characterized in that: The waste glass powder has a SiO2 content of 55%-70%, a CaO content of 10%-20%, and a Na2O content of 10-20%, wherein the particle size of the waste glass powder is not greater than 120 μm.

8. A method for preparing a high-efficiency chloride ion migration-blocking auxiliary gelling material according to any one of the preceding claims, characterized in that: The following steps are involved: S1. Weigh fly ash, slag, kaolin, activated desulfurized gypsum, CSH nanocrystalline core early strength agent and waste glass powder according to the required ratio to obtain a mixed dry material; S2. Stir the mixed dry materials at a rate of 60-80 rpm for 2-3 minutes to obtain the chloride ion efficient migration blocking auxiliary gelling material.

9. Use of the high-efficiency chloride ion migration blocking auxiliary cementitious material according to any one of claims 1 to 8 in cement concrete.

10. A method for applying the high-efficiency chloride ion migration blocking auxiliary cementitious material according to claim 9 in cement concrete, characterized in that: The following steps are involved: Step 1: Weigh cement and high-efficiency chloride ion migration blocking auxiliary cementitious material according to the required ratio, and stir at a speed of 60-80 rpm for 2-3 minutes to obtain a mixture; Step 2, adding water to the mixture obtained in step 1, stirring at a rate of 60-80 rpm for 2-3 minutes and then at a rate of 120-150 rpm for 5-6 minutes, pouring the slurry to fill the mold and vibrating it, removing the mold after curing for 1 day, sealing and curing, and obtaining cement concrete containing high-efficiency chloride ion migration blocking auxiliary cementitious material; The proportion of the cement, the high-efficiency chloride ion migration blocking auxiliary cementitious material and water, calculated by weight fraction, is: 100 parts of cement, 38-243 parts of the high-efficiency chloride ion migration blocking auxiliary cementitious material and 70 parts of water.

Citation Information

Patent Citations

  • A swelling-resistant microcapsule chloride ion curing agent, its preparation method and application

    CN109485296B

Cited By

  • Super-early-strength all-solid waste cementing material and preparation method thereof

    CN120887701A